THE ACADEMIC WRITING CHALLENGES FACED BY INDONESIAN UNDERGRADUATE EFL LEARNERS AT UNIVERSITY OF ISLAM MALANG - Sania Alinda Mouli Asnas (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
This study aimed to describe the academic writing challenges faced by students and how students can overcome their challenges. This study used a descriptive qualitative research design. This research was conducted on 55 English Education students in the 6th semester at University of Islam Malang. There were 5 out of 55 students who were interviewed. The purposive sampling was used in this study. In collecting data, the instrument used was the questionnaire and interview. The results showed that the students agreed that they had challenges in all the items of the questionnaire except for the part of writing conclusion which stated that it was neutral. Based on the results of interview, the students’ strategies to overcome their challenges using seven strategies such as brainstorming, reading many articles, using online applications, receiving feedback, writing practice, using the dictionary, editing their work by themselves. In conclusion, they faced challenges in terms of structure, developing ideas, vocabulary, and grammar.